(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
Trigonometric equations are mathematical expressions involving trigonometric functions like sine, cosine, and tangent. This book provides a comprehensive overview of trigonometric equations, covering various solution techniques and applications in mathematics and other disciplines. It offers clear explanations, examples, and exercises to help readers understand and master the concepts of solving trigonometric equations.